Inhibitory control expertise through sports practice: A scoping review - Simonet, M.; Beltrami, D.; Barral, J. (Journal of Sports Sciences, 2023)
The stopping of a planned motor response is called motor inhibitory control (IC) and allows humans to produce appropriate goal-directed behaviour. The ever-changing environment of many sports requires athletes to rapidly adapt to unpredictable situations in which split-second suppressions of planned or current actions are needed. In this scoping review, the approach of the PRISMA-ScR was used to determine whether sports practice develops IC and, if so, which sports factors are key to building IC expertise. The PubMed, Web of Science Core Collection, ScienceDirect and APA PsycNet Advanced Search databases were searched with predefined combinations of keywords. Twenty-six articles were selected and analysed. Most of the publications (n = 21) compared athletes with non-athletes, or athletes from other sports. Only a few articles (n = 5) reported results from intra-sport comparison. Overall, the studies reported better IC performance in athletes compared to non-athletes. The correlational link from sports practice to IC improvement is observed but additional longitudinal protocols are needed to prove its direct link. Findings have implication for determining whether IC could represent a marker of performance and thus for supporting the implementation of cognitive training in sport.